Influence of aggression on information processing in the emotional Stroop task - an event-related potential study - Bertsch, Katja; Böhnke, Robina; Kruk, Menno R.; Naumann, Ewald (Frontiers in Behavioral Neuroscience, 2009)
Aggression is a common behavior which has frequently been explained as involving changes in higher level information processing patterns. Although researchers have started only recently to investigate information processing in healthy individuals while engaged in aggressive behavior, the impact of aggression on information processing beyond an aggressive encounter remains unclear. In an event-related potential study, we investigated the processing of facial expressions (happy, angry, fearful, and neutral) in an emotional Stroop task after experimentally provoking aggressive behavior in healthy participants. Compared to a non-provoked group, these individuals showed increased early (P2) and late (P3) positive amplitudes for all facial expressions. For the P2 amplitude, the effect of provocation was greatest for threat-related expressions. Beyond this, a bias for emotional expressions, i.e., slower reaction times to all emotional expressions, was found in provoked participants with a high level of trait anger. These results indicate significant effects of aggression on information processing, which last beyond the aggressive encounter even in healthy participants.